Retorika Gubernur Provinsi Kalimantan Timur dalam Menghadapi Jurnalis Terkait Berita Lubang Tambang - Syafi'i, Abdullah; Juwita, Rina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study aims to determine and analyze the rhetoric of the Governor of East Kalimantan speaking in front of the mass media with the basis of Aristotle's theory as the researcher's standard. The theory used in this research is Aristotle's Rhetoric theory, in its development, rhetoric also includes the process of adjusting ideas to people and adjusting people to ideas through various kinds of messages. From the research results, it can be concluded that rhetoric plays an important role in public communication, especially in the context of political discourse through the mass media. The Governor of East Kalimantan, Isran Noor, with his straight-talking style, managed to use rhetoric effectively to influence public opinion, build relationships with the media, and inspire the public. In a situation that does not have an official communication team, the Governor is still able to manage his communication well and have a positive impact.